Koncept domu w powieściach dla młodzieży autorstwa Anny Łaciny = The concept of a home in novels for young people by Anna Łacina - Zotova, Nataliia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented article is devoted to the concept of a home in the novels of the contemporary Polish writer Anna Łacina ("Czynnik miłości", "Kradzione róże", "Telefony do przyjaciela", "Miłość pod Psią Gwiazdą", "Ostatnie wakacje"). On the material of selected texts, the multi?layered and autonomous concept of the home, its central, peripheral, opposing components in the linguacultural, anthropocentric and axiological perspective is examined.
Keywords: język; dom; koncept; chronotop; literatura familijna; literatura dla dzieci i młodzieży; idylla; zapach; language; home; concept; chronotope; family literature; literature for young people; idyll; fragrance